Language, Voice, and Performance: Notes on Lily Greenham’s Sound Poetry - Bello Minciacchi, Cecilia; Broqua, Vincent; Drucker, Johanna; Gardfors, Johan; Glaz Serup, Martin; McGovern, Fiona (Tidskrift för litteraturvetenskap, 2017)
Language, Voice, and Performance. Notes on Lily Greenham’s Sound Poetry In this collective article, we argue for a wider recognition of Lily Greenham’s sound poetry, underscoring her artistic uses of multi lingualism and transnational collaboration. The form of the article is conceptual: in order to signal the importance given to poetry as a collabo rative and transnational activity in Greenham’s oeuvre, we have chosen to write the article in six languages and as a collaboration between six scholars with different backgrounds. The form of the article moreover reflects the privilege given to language as material, structure, and activity in Greenham’s works. The purpose of our article is thus twofold: while we seek to initiate an academic reception of Greenham’s works and to highlight these as important contributions to the traditionally male-dominated historiography of sound poetry, we also seek to examine how academic writing can alter its conventional forms in order to address works that are not ideally suited for hermeneutic or exegetic acts of reading.